Photosynthetic Parameters and Oxidative Stress during Acclimation of Crepe-Myrtle (Lagerstroemia speciosa (L.) Pers.) in a meta-Topolin-Based Micropropagation System and Genetic Fidelity of Regenerated Plants - Naseem Ahmad; Nigar Fatima; Mohammad Faisal; Abdulrahman A. Alatar; Ranjith Pathirana (Plants, 2022)
An improved and stable micropropagation system using the cytokinin, meta-Topolin (N6 (3-hydroxybenzylamino purine—mT), with nodal explants in Lagerstroemia speciosa L. was established. Among the different doses of mT, the maximum number of shoots with the highest shoot length was obtained using Murashige and Skoog’s (MS) medium supplemented with 5.0 µM mT. The results were consistent throughout the proliferation period, when recorded at week 4, 8, and 12 of being cultured, with an average of 16.4 shoots per nodal explant, and having a mean length of 4.10 cm at week 8. Shoot proliferation rates could be further improved by a combination of 5.0 µM mT with 0.5 µM α-naphthalene acetic acid in MS medium; nodal explants produced an average of 24.3 shoots with a mean length of 5.74 cm after 8 weeks of being cultured. Among the five different concentrations of three auxins tested for the rooting of microshoots in MS medium, a 1.0 µM indole-3-butyric acid treatment was the best, with an average of 10.3 roots per microshoot at an average length of 3.56 cm in 93% of microshoots within 4 weeks of being transferred to this medium. A significant reduction of both chlorophyll a and b in leaves during the first week of acclimation corresponded with a high accumulation of malondialdehyde (MDH), indicating that lipid peroxidation affected chlorophyll pigments. From the second week of acclimation, photosynthetic pigment content significantly increased and MDH content decreased. The net photosynthetic rate and leaf carotenoid content showed almost linear increases throughout the acclimation period. Activity of antioxidant enzymes, namely, superoxide dismutase, catalase, and peroxidases, consistently increased throughout the acclimation period, corresponding with the accumulation of photosynthetic pigments, thus demonstrating the role of the improved antioxidant enzymatic defense system during acclimation. A comparison of parent plant DNA with that of the greenhouse acclimated plants using random amplified polymorphic DNA and inter-simple sequence repeat markers showed a monomorphic pattern indicating genetic stability and the suitability of the method for micropropagation of L. speciosa.